The Combined Effect of Attapulgite High Reactive Mineral Admixture and Superplastisizer on Compressive Strength of Attapulgite Lightweight Aggregate Concrete - Qais J. Frayyeh; Waleed A. Abbas; Ali K. Hassan (Engineering and Technology Journal, 2016)
The goal of this study , mainly is to investigate thecombined effects of using both Attapulgite high reactive mineral admixture and superplastisizer on the compressive strength of Attapulgite lightweight aggregate concrete ALWAC and some properties of sconcrete . The used coarse lightweight aggregate was made from Attapulgite clays with maximum size of 19 mm , and the optimum percentages of addition for both mineral and chemical admixture was 6% partial replacement from cement for Attapulgite mineral admixture and 0.5 L/100 kg cement for the superplastisizer used .The gained percentages of enhancement for compressive strength was (12.2%,12.6% and 16.3%) for curing ages of 7, 28 and 56 respectively as compared with the referenced plane mix when only the Attapulgite mineral admixture to be added , while the combined effect of both admixtures was clear by the percentages of ( 19.3% , 15.5% and 25% ) for curing ages 7,28 and 56 respectively as compared to the plane referenced mix . The obtained equilibrium density of ALWAC was 1818 kg/m3 ( ACI 213r-03 , less than 1840 kg/ m3 for structural purposes)for the concrete mix containing the two admixtures . The water absorption of ALWAC was reduced by the addition of the Attapulgite mineral admixture by (4% , 4.85% and 4.9% ) at 7,28 and 56 days of curing respectively but, using the superplastisizer cause an increase in water absorption and the percentages above get lowered to (2% , 3% and 2.6% ) at the ages of 7,28 and 56 days respectively .